Assimilation and turnover rates of lipid compounds in dominant Antarctic copepods fed with 13C-enriched diatoms. (15th June 2020) - Graeve, Martin; Boissonnot, Lauris; Niehoff, Barbara; Hagen, Wilhelm; Kattner, Gerhard
Abstract : The study revealed species- and stage-specific differences in lipid accumulation of the dominant Antarctic copepods, the primarily herbivorous Calanoides acutus (copepodite stage V (CV), females) and the more omnivorous Calanus propinquus (females) storing wax esters and triacylglycerols, respectively, which were collected in summer (end of December). Feeding carbon-labelled diatoms to these copepods, 13 C elucidated assimilation and turnover rates of copepod total lipids as well as specific fatty acids and alcohols. The 13 C incorporation was monitored by compound-specific stable isotope analysis (CSIA). CV stages of C. acutus exhibited an intense total lipid turnover and 55% of total lipids were labelled after 9 days of feeding. By contrast, total lipid assimilation of female C. acutus and C. propinquus was lower with 29% and 32%, respectively. The major dietary fatty acids 16:0, 16:1(n − 7) and 20:5(n − 3) had high turnover rates in all specimens. In C. acutus CV, the high rates of the de novo synthesized long-chain monounsaturated fatty acids and alcohols 20:1(n − 9) and 22:1(n − 11) indicate intense lipid deposition, whereas these rates were low in females. The differences in lipid assimilation and turnover clearly show that the copepod species exhibit a high variability and plasticity to adapt their lipid production to their various life phases. This article is part of the theme issue 'The next horizons for lipids as 'trophic biomarkers': evidence and significance of consumer modification of dietary fatty acids'.